1987
DOI: 10.1071/ch9871451
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthesis of the Lichen Depsidones Divaronic Acid and Stenosporonic Acid, and the Biosynthetic Implications

Abstract: The depsidones divaronic acid (24) (8-hydroxy-3-methoxy-1,6-dipropyl-11- oxo -11H- dibenzo [ b,e ][1,4]dioxepin-7-carboxylic acid) and stenosporonic acid (25) (8-hydroxy-3-methoxy-6-pentyl-l-propyl-ll-oxo-l1H-dibenzo[ b,e ][1,4]dioxepin-7-carboxylic acid) have been prepared by unambiguous synthesis, and have been shown to cooccur with colensoic acid, atranorin and chloroatranorin in the lichen Paraparmelia mongaensis. The syntheses employed a novel biomimetic-type approach which involved a Smiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…Se essa oxidação ocorre na posição 3, subseqüentes rearranjos do para-depsídeo formado conduzem a meta-depsídeos por migração do grupo acila 59. Se ocorrer oxidação na posição 5' seguida por uma migração de acila e subseqüente rearranjo tipo Smiles do meta-depsídeo formado, isso poderá conduzir às correspondentes depsidonas derivadas do orcinol 64 (Fig. 3).…”
Section: Meta-depsídeosunclassified
See 2 more Smart Citations
“…Se essa oxidação ocorre na posição 3, subseqüentes rearranjos do para-depsídeo formado conduzem a meta-depsídeos por migração do grupo acila 59. Se ocorrer oxidação na posição 5' seguida por uma migração de acila e subseqüente rearranjo tipo Smiles do meta-depsídeo formado, isso poderá conduzir às correspondentes depsidonas derivadas do orcinol 64 (Fig. 3).…”
Section: Meta-depsídeosunclassified
“…e Roccella galepagoensis Follm. foram isolados os glicosídeos rocelina [64], molina [65] e galapagina [66], cuja aglicona é uma cromona 75 .…”
Section: Cromonas Xantonas Naftoquinonas Antronas E Antraquinonasunclassified
See 1 more Smart Citation
“…This may be considered as evidence supporting the suggestion that depsidones can be modified after the formation of the ether bond. To explain the occurrence of iso-structural depside-depsidone pairs, Elix et al (1987) and Culberson & Elix (1989) suggested that the C-hydroxylation of a p-depside in the 5' position would be followed by acyl migration and a subsequent Smiles re-arrangement of the formed m-depside would lead to orcinol-depsidones. This hypothesis has been used to explain the biosynthesis of grayanic acid by the mycobiont of Cladonia grayi in axenic culture (Culberson & Armaleo 1992, Armaleo 1995.…”
Section: Depsidone Biosynthesismentioning
confidence: 99%
“…Mainly chlorolichens produce unique phenolic substances, depside, depsidones and some dibenzofurans, such as usnic acids (Huneck & Yoshimura, 1996), that are not produced by other fungi and plants, and that show some biological activities with interesting applications from a pharmacological point of view, mainly as antiviral agents or for dermatological treatments. Although semisynthetic organic processes have been attempted for the production of depsidones (Elix et al, 1987), they results very tedious, expensive and inappropriate for industrial applications. Alternatively, extraction from lichen thalli collected in nature implies a very high rate of biomass destruction which cannot be balanced because of the very slow rate of growth of these organisms.…”
Section: Introductionmentioning
confidence: 99%